THE ANALYSE OF STUDENTS’ ABILITY IN WRITINGDESCRIPTIVE TEXT AT THE VIII CLASS OF SMP NEGERI 1 BADAR IN THE ACADEMIC YEAR 2021/2022 - Fitriyah; Alvin Hadi; Muhammad Tahir (STKIP USMAN SAFRI KUTACANE, 2022)
This research aims to know the ability of the respondents in the VIII Class of SMPN 1 Badar in writing descriptive text and difficulties in writing descriptive text. The research employed qualitative research methods to find out what respondents’ challanges in writing descriptive text. The particpants of this reseacrh were 123 respondents which using Krejcie and Morgan. This research using test to see the respondents’ ability in writing descriptive text. The research data was collected through test with using rubrics; content, organization, grammar, vocabulary, and mechanics. The result of the data showed that many factors cause students to experience ptoblems in writing, especially in writing descriptive text. The average 45,02 of total respondents’ ability that indicated that only few of the respondents understood about the descriptive text. There were only 3 respondents who got the highest scores and the scores were 75 and 71,25. And only one respondents who got the score 75 from the total sampling were 123. It means that only 0,81% respondents have achieved the school KKM score of 75. However, there were 24 respondents who got the lowest scores and the scores were 32,5. Respondents have a low ability to write a descriptive text. Most respondents do not understand about how to write descriptive text and still confusing how to make it into English.This research found that each respondents had a different ability in writing descriptive text. This suggested that teacher could improve their teaching skill in the descriptive text in an interesting way.